2011
DOI: 10.1074/jbc.m110.154765
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin Ligase MYCBP2 Regulates Transient Receptor Potential Vanilloid Receptor 1 (TRPV1) Internalization through Inhibition of p38 MAPK Signaling

Abstract: The E3 ubiquitin ligase MYCBP2 negatively regulates neuronal growth, synaptogenesis, and synaptic strength. More recently it was shown that MYCBP2 is also involved in receptor and ion channel internalization. We found that mice with a MYCBP2-deficiency in peripheral sensory neurons show prolonged thermal hyperalgesia. Loss of MYCBP2 constitutively activated p38 MAPK and increased expression of several proteins involved in receptor trafficking. Surprisingly, loss of MYCBP2 inhibited internalization of transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 58 publications
1
40
0
Order By: Relevance
“…Recent studies have revealed that numerous ubiquitin ligases are involved in regulation of transcriptional factors including the MAPK signaling pathway and NF-B signaling pathway [29,30]. Moreover, some members of the TRIM family of ubiquitin ligases have been shown to be involved in the regulation of these signaling pathways [23,28,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that numerous ubiquitin ligases are involved in regulation of transcriptional factors including the MAPK signaling pathway and NF-B signaling pathway [29,30]. Moreover, some members of the TRIM family of ubiquitin ligases have been shown to be involved in the regulation of these signaling pathways [23,28,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…RotaRod experiment was performed to confirm the data obtained from the open field test. A cutoff time of 90 s was used for RotaRod experiments as practiced previously (Holland et al, 2011;Möser et al, 2015). Moreover, Nicol et al (2015) have recently reported that WT and GPR84 KO mice were unable to remain on the RotaRod apparatus for Ͼ100 s at a similar rate of rotation, supporting that 90 s is long enough to determine a motor deficit.…”
Section: Attenuation Of Cfa-induced Localized Inflammation and Pain Bmentioning
confidence: 99%
“…2A). MYCBP2 has been previously shown to mediate inflammatory hyperalgesia by altering neuronal functions in DRGs and spinal cords (12,20). Therefore, we determined RanGAP1 expression in DRGs from SNS Cre-negative MYCBP2 fl/fl mice during zymosan-induced hyperalgesia.…”
Section: Mycbp2mentioning
confidence: 94%
“…Determination of Protein Translocation and ExpressionThe cellular localization of MYCBP2, RanGAP1, or Ran was assessed as described previously (20). The experimenter was unaware of the treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation